The Importance of Plant Layout to Support the Smooth Process of Building Shelters After the Semeru Eruption - Emmy Ermawati (Jurnal Ilmu Manajemen Advantage, 2023)
The purpose of this study was to determine the importance of the right plant layout to support smooth development and to find out the obstacles in the process of building Huntara after the Semeru Eruption. This type of research is descriptive research with a qualitative approach where data obtained from a Huntara in Sumbermujur-Candipuro Village in the form of interviews and this analysis uses information systems from Huntara. The results of this study state that the role of plant layout in the development process is very important because it can support the smoothness of the development process. All of this if applied in accordance with the initial plan quickly the process of work in the construction of shelters will soon be completed and will soon be occupied by its residents. Because in this development process there are not only a few shelters but several thousand affected by Semeru. While the obstacles that occur in this development process are the first from the community itself and from the Non-Governmental Organization (NGO). If the community itself is constrained if they switch to a place that has been made by the government (huntara) this can interfere with the work they do everyday.